The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1165/rcmb.2013-0179oc
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycans Maintain Lung Stability in an Elastase-Treated Mouse Model of Emphysema

Abstract: Extracellular matrix remodeling and tissue rupture contribute to the progression of emphysema. Lung tissue elasticity is governed by the tensile stiffness of fibers and the compressive stiffness of proteoglycans. It is not known how proteoglycan remodeling affects tissue stability and destruction in emphysema. The objective of this study was to characterize the role of remodeled proteoglycans in alveolar stability and tissue destruction in emphysema. At 30 days after treatment with porcine pancreatic elastase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 46 publications
1
39
0
Order By: Relevance
“…The PGs normally contribute to the mechanical stability of the collagen-elastin network and prevent collapse of alveolar structures caused by electrostatic interactions from the negatively charged GAGs (81). Structural remodeling of the lung resulting from abnormal expression of PG-GAG complexes and structural changes to the GAG side chains can contribute to the development of pulmonary diseases (45,(83)(84)(85)(86)(87)(88).…”
Section: Proteoglycansmentioning
confidence: 99%
See 1 more Smart Citation
“…The PGs normally contribute to the mechanical stability of the collagen-elastin network and prevent collapse of alveolar structures caused by electrostatic interactions from the negatively charged GAGs (81). Structural remodeling of the lung resulting from abnormal expression of PG-GAG complexes and structural changes to the GAG side chains can contribute to the development of pulmonary diseases (45,(83)(84)(85)(86)(87)(88).…”
Section: Proteoglycansmentioning
confidence: 99%
“…Other studies have shown that low molecular weight HA fragments create a proinflammatory state by stimulating macrophages to release chemokines and MMPs (specifically, MMP-12), resulting in chronic inflammation, destruction of the lung parenchyma, and airway wall remodeling in emphysema (101,102). In a recent study using a mouse model of porcine pancreatic elastase-induced emphysema, the loss of the structural role of PGs related to the change in charge density on the GAGs reduced alveolar stability and led to a more progressive disease phenotype (85). In that study, the changes in mouse lung tissue stiffness and the alveolar shape distortion under the influence of varying tonicity conditions were increased in experimental emphysema, thus suggesting that the loss of PGs affects lung tissue stability and the progression of emphysema.…”
Section: Glycosaminoglycansmentioning
confidence: 99%
“…Because of their highly sulfated and negatively charged carbohydrate groups, GAGs have the capacity to hold large quantities of water. Only a few studies have investigated the mechanics of PGs in the lung [1,27,59,145]. Perhaps the most important role the PGs play in mechanics is that they hinder the alignment of fibers in the ECM during stretch [27].…”
Section: Aging Of the Proteoglycansmentioning
confidence: 99%
“…Note, the reduction of GAG density and chain length in the adult aggrecan. Based on morphometric and biochemical analyses complemented with computational modeling, a loss of PGs has been predicted to promote the progression of heterogeneous airspace enlargement in emphysema [145]. It remains to be shown whether the loss of GAGs during aging contribute to the characteristic homogeneous airspace enlargement ( Fig.…”
Section: Aging Of the Proteoglycansmentioning
confidence: 99%
“…A wide variety of studies have highlighted the proteolytic activity of elastase in causing structural changes, such as higher mean linear intercept and alveolar enlargement both in mice [71][72][73][74][75] and in rats [76][77][78][79] (Table 2). Furthermore, several studies reported changes in ECM composition after elastase administration, such as disorganized elastin [80,81], degradation of proteoglycans [82], and abnormal collagen remodeling [83][84][85][86][87][88]. However, as in CS models, these effects are dependent on several factors, including strain; enzyme dose at each instillation; and number of elastase challenges (Figure 2).…”
Section: Elastase Instillationmentioning
confidence: 99%